2016
DOI: 10.1111/cas.13000
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐escalation study of tabalumab with bortezomib and dexamethasone in Japanese patients with multiple myeloma

Abstract: B‐cell activating factor (BAFF) promotes the survival and adhesion of multiple myeloma (MM) cells. Tabalumab (LY2127399) is an anti‐BAFF monoclonal antibody. This phase 1, multicenter, open‐label, nonrandomized, dose‐escalation study evaluated the safety, tolerability, pharmacokinetics, pharmacodynamics and efficacy of tabalumab in combination with bortezomib and dexamethasone in Japanese patients with relapsed or refractory MM (RRMM). Sixteen patients received intravenous i.v. tabalumab 100 mg (Cohort 1, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Rossi et al evaluated atacicept as monotherapy in 12 patients who had failed 5 prior lines of therapy and no OR was achieved [65]. Shinsuki et al studied tabalumab in doses of 100-200 mg in combination with Vd in RRMM patients with 1-5 prior lines of therapy and reported a combined OR of 56.3% and tabalumab was well tolerated [66]. Raje et al studied tabalumab 100mg, 300mg and placebo + Vd each and found no statistically significant difference between OR and PFS.…”
Section: Resultsmentioning
confidence: 99%
“…Rossi et al evaluated atacicept as monotherapy in 12 patients who had failed 5 prior lines of therapy and no OR was achieved [65]. Shinsuki et al studied tabalumab in doses of 100-200 mg in combination with Vd in RRMM patients with 1-5 prior lines of therapy and reported a combined OR of 56.3% and tabalumab was well tolerated [66]. Raje et al studied tabalumab 100mg, 300mg and placebo + Vd each and found no statistically significant difference between OR and PFS.…”
Section: Resultsmentioning
confidence: 99%
“…Tabalumab, an mAb against B-cell activating factor (BAFF), has been tested in a dose-escalation phase I study in combination Vd in RRMM. The combination was well tolerated with an ORR of 56% 54 . However, a phase II study of tabalumab 100 or 300 mg in combination with Vd failed to show an improvement in the PFS of patients with tabalumab and Vd compared to the placebo-Vd arm 55 .…”
Section: Targets For Mabs In the Treatment Of MMmentioning
confidence: 94%
“…Treatment of mice with tabalumab resulted in a significant reduction in tumor burden, prolonged survival, decreased osteoclast recruitment and activation, which caused fewer lytic lesions in the bone by a reduction in NF-κB signaling [ 154 ]. In Phase I studies, tabalumab in combination with bortezomib was well tolerated for patients with relapsed/refractory MM [ 147 , 148 ]. In a Phase II trial, patients with relapsed/refractory multiple myeloma were randomly assigned 1:1:1 to receive placebo, tabalumab 100 mg, or tabalumab 300 mg, each in combination with dexamethasone and bortezomib.…”
Section: Novel Therapeutic Agents In Preclinical Research and Ongoing...mentioning
confidence: 99%